Andrzej K. Piasecki, Referenda w III Rzeczypospolitej, 2005 - Krzywoszyński, Przemysław (Czasopismo Prawno-Historyczne, 2008)
Recenzja: Andrzej K. Piasecki, Referenda w III Rzeczypospolitej, Wydawnictwo Naukowe PWN, Warszawa 2005, ss. 192